Small Extracellular Vesicles Secreted by iPSC-Derived MSCs Ameliorate Pulmonary Inflammation and Lung Injury Induced by Sepsis through Delivery of miR-125b-5p - Wei Peng; Yun Yang; Jiaquan Chen; Zeyao Xu; Yuanlei Lou; Qi Li; Ning Zhao; Kejian Qian; Fen Liu (Journal of Immunology Research)
Background. Sepsis-induced acute lung injury is a common critical illness in intensive care units with no effective treatment is currently available. Small extracellular vesicles, secreted by mesenchymal stem cells (MSCs), derived from human-induced pluripotent stem cells (iMSC-sEV), possess striking advantages when incorporated MSCs and iPSCs, which are considered extremely promising cell-free therapeutic agents. However, no studies have yet been conducted to systemically examine the effects and underlying mechanisms of iMSC-sEV application on attenuated lung injury under sepsis conditions. Method. iMSC-sEV were intraperitoneally administered in a rat septic lung injury model induced by cecal ligation and puncture (CLP). The efficacy of iMSC-sEV was assessed by histology, immunohistochemistry, and pro-inflammatory cytokines of bronchoalveolar lavage fluid. We also evaluated the in vitro effects of iMSC-sEV on the activation of the inflammatory response in alveolar macrophages (AMs). Small RNA sequencing was utilized to detect changes in the miRNA expression profile in lipopolysaccharide (LPS)-treated AMs after iMSC-sEV administration. The effects of miR-125b-5p on the function of AMs were studied. Results. iMSC-sEV were able to attenuate pulmonary inflammation and lung injury following CLP-induced lung injury. iMSC-sEV were internalized by AMs and alleviated the release of inflammatory factors by inactivating the NF-κB signaling pathway. Moreover, miR-125b-5p showed a fold-change in LPS-treated AMs after iMSC-sEV administration and was enriched in iMSC-sEV. Mechanistically, iMSC-sEV transmitted miR-125b-5p into LPS-treated AMs to target TRAF6. Conclusion. Our findings demonstrated that iMSC-sEV treatment protects against septic lung injury and exerts anti-inflammatory effects on AMs at least partially through miR-125b-5p, suggesting that iMSC-sEV may provide a novel cell-free strategy for the treatment of septic lung injury.